KEABSAHAN AKTA IKRAR WAKAF DARI TANAH YANG SUDAH BERSTATUS FASILITAS SOSIAL (STUDI KASUS AKTA IKRAR WAKAF NOMOR W2/07/VII/2019) - Putra, Ade; Yulia Mirwati; Yasniwati (Yuriska: Jurnal Ilmiah Hukum, 2024)
Background: The registration of the Deed of Pledge of Endowment (Akta Ikrar Wakaf) is crucial to ensure the validity and clarity of the waqf land status. Issues arise when the deed of waqf pledge for land that already has a social facility status was rejected by the Land Office in 2019. Research Metodes: This research is categorized as empirical legal research that is descriptive-analytical in nature, drawing from secondary legal materials and tertiary legal sources. Findings: The research findings include: 1) The validity of the Deed of Pledge of Waqf No. W2/07/VII/2019 complies with regulations, but the waqf pledge is invalid due to unmet waqf elements. 2) Registration constraints of the Deed of Pledge of Waqf lead to legal uncertainty and the risk of revocation of ownership rights or waqf status. Conclusion: This research concludes that the Deed of Pledge of Waqf No. W2/07/VII/2019 related to social facility land is not valid, and the registration constraints can have serious consequences, including legal uncertainty and the risk of revocation of ownership rights. The proposed solution is to transfer the land to the city government as a municipal asset to address these issues.